Evaluation of a semi-structured model for the medication therapy management record in the hospital setting - Luna E. Ferreira (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Introduction: The record of the activities performed by the health professional should compose the patient’s medical record, whose fundamental role is communication. One way to make registration easier is to create semi-structured models. Objective: To evaluate the applicability and reproducibility of a semi-structured model for the medication therapy management record in hospitals. Methods: A convenience sampling of fifteen clinical pharmacists working in public hospitals in Minas Gerais was used. The participants received the semi-structured model for medical record and detailed report of two simulated clinical cases. The records made by each participant were compared to a standard record - template and the verification items were evaluated and categorized into: 1- compliant, 2- partially compliant, and 3- non-compliant. Participants also answered an electronic questionnaire with questions related to clinical experience and training. The main variable evaluated was the compliance percentage, considering the total of items evaluated. And for all variables under study, absolute and relative frequency were determined. The influence of the participants’ individual characteristics was univariate analyzed. Results: Most of the group (58%) had been graduated in Pharmacy for over ten years and most (83%) reported having been trained in the clinical area. The characteristics of the participants did not affect the results obtained. The overall compliance percentage showed a good performance of pharmacists using this model (76%) and most participants considered the model to be highly applicable / useful (75%). Conclusion: The high percentage of compliance achieved demonstrates that the semi-structured medical record model developed in this study was considered applicable by most participants, who also had a good performance in its use, and may be a starting point for other pharmacists and services to develop their own models, adapted to the reality of each service.